2011
DOI: 10.1590/s0006-87052011000300023
|View full text |Cite
|
Sign up to set email alerts
|

Atmosfera modificada em laranja 'Pêra' minimamente processada

Abstract: Este trabalho teve como objetivo determinar a influência da embalagem com atmosfera modificada na manutenção da qualidade de laranja 'Pêra' minimamente processada armazenada sob refrigeração. As laranjas descascadas foram acondicionadas em filme de polipropileno de 32 µm sob atmosfera modificada passiva ou ativa (5% O2 + 10% CO2; balanço N2). Laranjas acondicionadas em bandeja de poliestireno expandido revestida com filme de cloreto de polivinila de 20 µm foram utilizadas como controle. O armazenamento dos fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 16 publications
(11 reference statements)
2
7
0
8
Order By: Relevance
“…This response profile may indicate the consumption of these compounds by the respiratory process, which tends to increase after the processing of the fruits. Furthermore, these results are in agreement with those found for minimally processed 'Marisol' mandarin (TIBOLA et al, 2006), minimally processed 'Ponkan' mandarin (PINTO; VILAS BOAS; DAMIANI, 2007), minimally processed tangelo 'Minneola' (DEL CARO et al, 2004), and minimally processed 'Pera' orange (ARRUDA et al, 2011). Different behavior profile was observed for the uncoated fruits and those coated with gelatin-based film, in which there was little tendency to TSS TIBOLA et al, 2006;PINTO;VILAS BOAS;DAMIANI, 2007;PLAZA et al, 2011).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…This response profile may indicate the consumption of these compounds by the respiratory process, which tends to increase after the processing of the fruits. Furthermore, these results are in agreement with those found for minimally processed 'Marisol' mandarin (TIBOLA et al, 2006), minimally processed 'Ponkan' mandarin (PINTO; VILAS BOAS; DAMIANI, 2007), minimally processed tangelo 'Minneola' (DEL CARO et al, 2004), and minimally processed 'Pera' orange (ARRUDA et al, 2011). Different behavior profile was observed for the uncoated fruits and those coated with gelatin-based film, in which there was little tendency to TSS TIBOLA et al, 2006;PINTO;VILAS BOAS;DAMIANI, 2007;PLAZA et al, 2011).…”
Section: Resultssupporting
confidence: 85%
“…This reduction in the TA profile during storage, regardless of the treatment, was also observed by Leme et al (2007) in "Pera" oranges and in oranges from Portugal by Rocha et al (1995). On the other hand, some studies involving minimally processed citrus fruits reported no changes in the content of this parameter during the evaluation periods (ARRUDA et al, 2011;PRETEL et al, 1998;KLUGE et al, 2003;DONADON et al, 2004;GROPPO et al, 2009). …”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…The mechanical damage caused by peeling, cutting and slicing increase respiratory activity and ethylene production, especially in the first hours after processing. Injured cells presence and cellular component loss during processing operations favor microorganism development (Arruda et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A laranja foi disseminada pelo mundo, sofrendo mutações, originando novas variedades, com alterações no sabor, aroma, cor e tamanho (MATTE et al, 2006;ARRUDA et al, 2011).…”
Section: Introductionunclassified